2013
DOI: 10.1021/bc4000614
|View full text |Cite
|
Sign up to set email alerts
|

Protected Maleimide Building Blocks for the Decoration of Peptides, Peptoids, and Peptide Nucleic Acids

Abstract: Monomers allowing for the introduction of [2,5-dimethylfuran]-protected maleimides into polyamides such as peptides, peptide nucleic acids and peptoids were prepared, as well as the corresponding oligomers. Suitable maleimide deprotection conditions were established in each case. The stability of the adducts generated by Michael-type maleimide-thiol reaction and Diels-Alder cycloaddition to maleimide deprotection conditions was exploited to prepare a variety of conjugates from peptide and PNA scaffolds incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…General Procedure for the Synthesis of Tert-butyl-(2-hydroxyethyl)carbamate 3a and Its Derivatives (3b-e) [25][26][27][28][29] To a solution of 2a (or 2b-e, 20 mmol) in a mixture of dioxane (15 mL) and H 2 O (7 mL), was added 5N NaOH (4.8 mL) and a solution of Boc 2 O (5.0 g, 23 mmol) in dioxane at 0 °C. After stirred at rt overnight, the reaction mixture was concentrated in vacuo.…”
Section: Chemistrymentioning
confidence: 99%
“…General Procedure for the Synthesis of Tert-butyl-(2-hydroxyethyl)carbamate 3a and Its Derivatives (3b-e) [25][26][27][28][29] To a solution of 2a (or 2b-e, 20 mmol) in a mixture of dioxane (15 mL) and H 2 O (7 mL), was added 5N NaOH (4.8 mL) and a solution of Boc 2 O (5.0 g, 23 mmol) in dioxane at 0 °C. After stirred at rt overnight, the reaction mixture was concentrated in vacuo.…”
Section: Chemistrymentioning
confidence: 99%
“…However, since we had observed that the quality of cyclic peptide crudes was a bit lower when cyclization took place upon treatment with TFA, 22 we incorporated the 2,5-dimethylfuran-protected maleimidopropanoic acid. 27 To introduce maleimide moieties at other positions of the chain, 2-[(2,5-dimethylfuranprotected) maleimide]-1-aminoethane 23 should be employed. In the absence of two orthogonal maleimide protecting groups, this precludes use of maleimides for subsequent conjugation.…”
Section: Methodsmentioning
confidence: 99%
“…23 When the peptide is linear, H 2 O 2 oxidizes the free thiol to sulfonic acid (and the mass increases 48 units), whereas when the peptide is cyclic the thioether is oxidized to sulfoxide (and the mass increases 16 units).…”
Section: Assessment Of Cyclization: Reaction With H 2 O 2 Formationmentioning
confidence: 99%
“…exo-3,6-dimethyl-3,6-epoxi-1,2,3,6-tetrahydrophthalimide (1) was prepared following the previous report of Elduque, X. et al 10 , introducing slightly modifications; the more remarkable feature of the 1 H NMR spectrum for (1) reported by Elduque is the assignation done to the double bond protons (i.e. the CH protons located at positions 4 and 5) they were assigned at 6.31 ppm for both the exo and the endo isomers.…”
Section: 1mentioning
confidence: 99%
“…thermal or light irradiation) 9 . As a thermally labile protecting group has been included in synthetic schemes to provide for peptides, peptoids and peptide nucleic acids 10 and Maleimide functionalized gold nanoparticles 11,12 . From the structural point of view, the DA adducts between Furan and Maleimide, has been studied mainly for its N-substituted analogs, thus in this way the X-ray crystallography of the N-amino 13,14 , N-acetoxyphenyl 15 and N-aryl 16 has been studied; Surprisingly, for the DA adduct of 2,5-dimethylfuran and Maleimide the molecular structure has not been determined using X-ray diffraction analysis.…”
Section: Introductionmentioning
confidence: 99%